Integrated Reporting and Firm Value in an Emerging Economy: The Moderating Role of Firm Size - Manimore Makri; Kailash Chandra Kabra (Universitas Pasundan, 2023)
This paper aims to investigate the relationship between Integrated Reporting Quality and Firm Value in the presence of a moderating variable, Firm Size. The study uses a market capitalization-based sample of the top 100 companies listed on Bombay Stock Exchange for the years 2017-2018 to 2019-2020. Partial Least Squares- Structural Equation Model (PLS-SEM) has been applied to observe the relationship between IRQ & FV, as well as the moderating effect of FS. The analysis confirms Stakeholder Theory by presenting a significant positive relationship between Integrated Reporting Quality & Firm Value. The insignificant effect of Firm Size as a moderator between IRQ and FV shows that Indian firms irrespective of their size disclose qualitative IR. The study presents one of the first investigations in the context of India on the relationship between IR & FV while moderating for FS. The study is beneficial for companies to understand the firm performance benefits of voluntary reporting such as IR.